Adolescent Sexual Behaviour At Risk of Unintended Pregnancy And HIV/AIDS (Universitas Negeri Semarang, 2018)
Irresponsible sexual activity in adolescence around the world puts teenagers at risk challenges to various reproductive health problems. The purpose of this study was to determine the factors related to the adolescents sexual behaviour at risk of Unintended Pregnancy (KTD) and HIV / AIDS in a Senior High School of Konawe Islands District. The type of the research was mix method research which was a combination between quantitative and qualitative research with sequential explanatory design. The population of this study consisted of 867 people with quantitative samples of 269 people and qualitative samples of 5 people by using purposive sampling technique. Quantitative data analysis technique used Chi-Square test, while qualitative data analysis technique used data reduction, data display and data verification. The Research results showed that there were 5.9% of adolescents had risky sexual behaviors toward the unintended pregnancy (KTD) and HIV / AIDS. Bivariate analysis using chi-square test showed that there were six variables that significantly correlated with adolescents sexual behavior at risk of unintended pregnancy (KTD) and HIV / AIDS; which were knowledge (sig .0,010), adolescent attitude (sig. 0,000), parent role (sig .028), peer influence (sig. 0,000), courtship style (sig .023), and information media (sig. 0,000). Qualitative analysis showed the attitude variable as the factor that gave the highest risk in risky sexual behavior among adolescents. The conclusion was that there was relationship between knowledge, attitude, parent role, peer influence, courtship style and information media. It is suggested to the Schools to improve good and appropriate basic knowledge and understanding of adolescents about the prevention of risky sexual behavior, and good and strict supervision and guidance on the adolescents' activities for well controlled adolescents behavior. Kata kunci: Remaja, Perilaku seksual, Kesehatan reproduksi.